Determinación de la incidencia de Ancylostoma caninum en la parroquia Camilo Ponce en la ciudad de Babahoyo - Oñate Morales, Ariel David (2023)
This experimental work was carried out in the parish of Camilo Ponce in the city of Babahoyo with the intention of demonstrating whether or not there is an incidence of Ancylostoma caninum. Remembering that a parasite is any living organism that takes advantage of another without causing more or less apparent harm, the incidence of Ancylostoma caninum was determined with a random sampling of pets that attended the Ramirez veterinary center, of which a total of 100 canines were analyzed. Within the analysis of the stool samples, it was found that 31% were positive for Ancylostoma caninum cysts, and to improve the study, the positive cases were analyzed according to age, sex and habitat. In the analysis we found that within the sex category, the males presented a higher infection rate of 19 positive cases as opposed to 12 positive cases in the females. When analyzing the age of the pets, we observed that the highest number of positive cases was in the range of 1 to 9 months of age with 14 positive cases and between 19 months and older, although the age with the lowest number of positive cases was 10 to 18 months. To better quantify the results and the incidence, we also took into account the factors of the habitat of the pets and their breeds, where it is reflected that the pets that spend the most time in free spaces or are outside their homes are the mestizos, which were the ones with the highest percentage of positive cases.